Pemanfaatan Informasi Covid-19 Di Gampong Beurawe, Banda Aceh - Hz, M. Khalilullah; Nengsih, Sri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to analyze the use of Covid-19 information technology in Beurawe Village, Banda Aceh, in the midst of the corona virus pandemic and the results of the study show that the use of information technology has a very important role in people's understanding in order to be able to understand and prevent the spread of Covid-19. The Beurawe Village community must really understand the Covid-19 information conveyed. Understanding alone is not enough if there is no action to break the Covid-19 chain. With the information technology that is currently developing rapidly, including information media and internet networks that can connect the government and the Beurawe village community so that the socialization process to the community can run well and quickly as it should, even though in the midst of the COVID-19 pandemic, which limits activities.